The Frankliniella fauna of Brazil: additions and updated key to species (Thysanoptera: Thripidae) - Lima, Élison Fabrício Bezerra; Miyasato, Elisa Aiko (Zootaxa, 2017)
Frankliniella bambusae n. sp., F. catharinensis n. sp. and F. piauhyensis n. sp. are described from Brazil, also the first description of the male of F. caseariae Moulton. Newly recorded from Brazil is F. parvula Hood, together with comments on F. tritici (Fitch) and F. musaeperda Hood, and an updated key is provided to the 45 Frankliniella species now known from Brazil. In addition, a key to Frankliniella species whose females have pore plates on sternite III is appended.